Вимірювальні комірки та структури для дослідження вологовмісних матеріалів - Глухі, М. А. (ХНУРЕ, 2024)
The main requirements for measuring cells and structures intended for microwave research of moisture-containing materials are considered. Examples of possible experimental measuring structures and stages of their practical implementation are given.
Keywords: дослідження вологовмісних матеріалів; moisture-containing materials